If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -24 = 6x Reorder the terms: -24 + 8x = 6x Solving -24 + 8x = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -24 + 8x + -6x = 6x + -6x Combine like terms: 8x + -6x = 2x -24 + 2x = 6x + -6x Combine like terms: 6x + -6x = 0 -24 + 2x = 0 Add '24' to each side of the equation. -24 + 24 + 2x = 0 + 24 Combine like terms: -24 + 24 = 0 0 + 2x = 0 + 24 2x = 0 + 24 Combine like terms: 0 + 24 = 24 2x = 24 Divide each side by '2'. x = 12 Simplifying x = 12
| -48h^8/-8h^2 | | (x-10)=2x | | 5x+15=-3x-16 | | 83-5y=3 | | 8-6x=4x+49 | | x/2+2=15 | | 14x-6x=72 | | log(5x)=log(x-1)+1 | | 4(x+4)=4(x+15) | | -(x+4)=-2(3x+16) | | 6x-y-5=0 | | 6(x+5)=6(x+11) | | 45=-5x | | 4(4x+3)=15x+10 | | 4x+2+3x=5x+14+x | | a^3+b^3+c^3=21 | | 9t=-10t-3 | | -5(2x-9)=2(x-8)11 | | 20x^3+8x^2+12x= | | 4-18=z/-9 | | 12x-8=11x | | 2x^2+8x+6=8 | | 9w-8w+2=-4+2w | | 3/4c=72 | | 5j-440=30 | | 3D-10=6-5d | | -3(x-4)=-1 | | 10+c-8c=-10-3c | | 8x+12=-6x-16 | | -6(2)(-1)(-1)= | | y=niga | | 0=x^2-192X+1080 |